Persepsi Publik pada Pengelolaan Taman Kota di Kota Bandung - Tomi Setiawan; Sintaningrum Sintaningrum; Dartho Mirandia (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2017)
This study is intended to explore the public perception, especially visitors of a city park to express their aspirations. Data collection techniques that was employed in this research are observation, questionnaire and interview and literature study. The results showed that the general public perception of the city park in the city of Bandung is quite good, but other respondents have opposite perception. They perceive that the management of city parks are not well maintained, less clean and incomplete in infrastructures, and the maintenance of the park is still incidentally maintained by agency managers. Secondly, there is a fact that there are no institutional system that can accommodate all stakeholders in the management of city parks. It is therefore important for the government of Bandung to immediately review the policies regarding the city park by considering participatory programs with existing policies. The review identifies various other policies needed